Pengaruh Profitabilitas, Leverage, dan Kepemilikan Institusional Pada Tax Avoidance - Arianandini, Putu Winning; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p17, 2018)
Companies are trying to lower their tax costs in order to earn a higher profit. This study aims to examine the effect of profitability, leverage, and institutional ownership of tax avoidance. This study focused on manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2012-2016 with a population of 157 companies. Determination of the number of samples using purposive sampling method, samples obtained by 39 manufacturing companies. Hypothesis testing is done by multiple linear regression analysis technique. Hypothesis testing method using significance level of 5%. This study obtained the first result, the profitability variable negatively affect the tax avoidance. The second result, on the leverage variables has no effect on tax avoidance. The third result, the institutional ownership variable has no effect on tax avoidance. Keywords: Profitability, leverage, institutional ownership, tax avoidance.